2012
DOI: 10.1039/c1fd00061f
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear vibrational spectroscopic studies on water/ionic liquid([Cnmim]TFSA: n = 4, 8) interfaces

Abstract: The interfaces of water/room temperature ionic liquids (RTIL) (1-alkyl-3-methyl imidazolium bis(trifluoromethylsulfonyl)amide ([C(n)mim]TFSA): n = 4, 8) are investigated by infrared-visible sum frequency generation (IV-SFG) vibrational spectroscopy and molecular dynamics (MD) simulation. SFG spectra taken within the SO stretch region drastically differ between air/RTIL and water/RTIL interfaces. When a RTIL surface is in contact with water, a broadened and blue-shifted SO2-ss mode peak is observed in the SFG s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 53 publications
2
23
1
Order By: Relevance
“…This conclusion is different from findings of former studies that concluded the NTf − 2 anions' both CF 3 groups point exclusively outwards to the vapor phases parallel with the surface normal. 8,11,18,19 We explain this by the rougher analysis performed in those studies that considered only the average orientation instead of a distribution of possible orientations. At the BMIM NTf 2 -water interface however this second peak becomes dominant implying that apolar "arms" have a high tendency to point inward.…”
Section: Orientation Analysis Of Interface Moleculesmentioning
confidence: 99%
“…This conclusion is different from findings of former studies that concluded the NTf − 2 anions' both CF 3 groups point exclusively outwards to the vapor phases parallel with the surface normal. 8,11,18,19 We explain this by the rougher analysis performed in those studies that considered only the average orientation instead of a distribution of possible orientations. At the BMIM NTf 2 -water interface however this second peak becomes dominant implying that apolar "arms" have a high tendency to point inward.…”
Section: Orientation Analysis Of Interface Moleculesmentioning
confidence: 99%
“…Experimental spectroscopy [25,[48][49][50][51][52][53][54][55][56][57], small angle X-ray or neutron diffraction (SAXS/SANS) [58][59][60][61][62][63][64][65], and nuclear magnetic resonance (NMR) studies [66][67][68][69][70][71] have revealed a wealth of information on the structural and dynamic properties of IL/water mixtures. We restrict such synopsis to ILs composed of shorter chain cations similar to BMIM + ; it is well-documented that ILs composed of longer chain cations form micelles, reverse micelles or self-assemble when mixed with water [53,58,60,[72][73][74] but this surfactant-like regime is not our focus.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational red shifts of water indicate how hydrogen bonding/structure is altered by local environment and have been characterized in a variety of ILs at dilute water concentrations [25,52] and as a function of water content [50,56]. Under dilute conditions, spectroscopic measurements indicate that water molecules interact primarily with the anions within both hydrophobic and hydrophilic ILs [49,51]. At higher water concentration within hydrophilic IL/water mixtures, a number of different peaks were observed for the water stretch (deuterated) [50], with relative populations being significantly concentration dependent and suggesting the formation of water domains or clusters [56].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, next to an interface (solid-liquid, [30][31][32][33][34][35][36] air-liquid [37][38][39] or liquid-liquid [40,41] ), nanostructure closely related to, but more ordered than, the bulk phase is formed. This is because the second surface orients and aligns the pre-existing ion arrangement.…”
Section: Introduction-mentioning
confidence: 99%